Interfacial crosslinking for highly thermally conductive and mechanically strong boron nitride/aramid nanofiber composite film. (December 2021) - Mo, Rui; Liu, Zhongjie; Guo, Wenyao; Wu, Xinfeng; Xu, Qunjie; Min, Yulin; Fan, Jinchen; Yu, Jinhong
Abstract: Always, the interfacial thermal resistance and the phonons scattering greatly restrict the further improvement of boron nitride nanosheets (BNNS)/polymer composites. Herein, the interfacial crosslinking approach was innovatively used to enhance the in-plane thermal conductivity (TC) and mechanical properties of the BNNS/ANFs composites. In order to achieve the interfacial crosslinking, the BNNS was aminated via melting functionalization with urea and the ANFs were activated by hydrolysis with phosphoric acid (PA). The nacre-like cross-linked aminated BNNS/reactive ANFs (C-ABNNs/R-ANFs) composite film was fabricated by vacuum-assisted filtration followed with interfacial crosslinked by condensation reaction with glutaraldehyde (GA). The interfacial crosslinking effectively reduced the interfacial thermal resistance and phonons scattering, simultaneously contributes to the stress transfer between ABNNs and R-ANFs. When the loading amount of ABNNs is 20 wt%, the in-plane TC of the C-ABNNs/R-ANFs composite film is ∼10.15 W m −1 K −1 which is nearly two times higher than that of ABNNs/R-ANFs composite film (∼5.59 W m −1 K −1 ). Graphical abstract: Image 1 Highlights: The C-ABNNs/R-ANFs film is prepared by vacuum-assisted filtration followed with interfacial crosslinking by glutaraldehyde. The interfacial crosslinking significantly improved the mechanical property and thermal conductivity. The interfacial crosslinking promotes the stress transfer. The interfacial thermal resistance and phonons scattering were reduced after interfacial crosslinking.